Pedeutologia systemologiczna od schematu do kreatywności w pedagogice = Systemological pedeutology from schematic acting to creativity in pedagogy - Duraj-Nowakowa, Krystyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper is an attempt to perceive pedeutology in systemological perspective on the way from technology and schematic models to humanistic approaches, through non-pattern acting and creativity. Materials from both sub-disciplines - pedeutology and methodology of sciences - serve here as a sphere of cognition. In both of them, important data of double provenance can be found: first, in outstanding authors` social and humanistic writings; secondly, in (after being confronted with the previous ones) the author of this article`s and the closest circle of her colleagues` scientific writings gained from the last 35 years of collective study and research investigations.
Keywords: aplikacje teorii systemow; pedagogika systemologiczna; pedeutologia systemologiczna; applications of the theory of systems; systemological pedagogy; systemological pedeutology